Hygienic substantiation of calculating models for prognosis of toxicity of different classes insecticides (second part) - O.P. Vavrinevych; B.I. Shpak; A.M. Antonenko; S.T. Omelchuk; T.I. Zinchenko (Medičnì Perspektivi)
This work is the second part of our study to develop alternative experimental mathematic models for predecting toxicity of insecticides, where we carried out a statistical analysis and comparative estimation of the toxicometric parameters obtained experimentally and calculated according to the proposed equations. In the first stage calculations were carried out and the most reliable models were proposed. The purpose of the research is the scientific substantiation and statistical analysis of the calculation models for predicting the toxicity of insecticides of different classes. For research we took the insecticides of the following chemical classes: neonicotinoids, pyrethroids, organophosphorus compounds. Statistical analysis of the linear and nonlinear regression equations obtained for insecticides was conducted. The equations described the dependence of subthreshold doses in the chronic experiment of all insecticides, the median lethal doses at oral admission of pyrithoids and neonicotinoids from molecular weight; and toxicometry parameters of all insecticides and their individual groups (pyrithoids, neonicotinoids, organophosphorus compounds) on melting temperature and the octanol-water partition coefficient. On the basis of a comparison of the toxicometry parameters obtained experimentally (actual parameters) and calculated according to the proposed equations checking of possibility of using of the calculating models for predicting the danger of the investigated groups of insecticides was performed. For substantiated pairs of resultant and factorial variables for pyrethroids, neonicotinoids, and organophosphorus pesticides a reliable correlation was established (ractucal> rtable at p = 0.05) or trend (ractucal> rtable at p = 0.1). A good and very good consistency of the features selected for the calculations according to the Cronbach’s alpha (index ranged from 0.8 and above) was indicated. The developed algorithm makes it possible to significantly simplify the conduction of toxicological studies of the studied classes of insecticides